Zikir Al-Ma`tsurat sebagai Media Ketenangan Psikososial Remaja - Galih Habibati Kusuma (Gunung Djati Conference Series, 2023)
This paper discusses zikr al-ma'tsurat as a medium of adolescent psychosocial tranquility. This study aims to discuss zikr al-Ma'tsurat as the psychosocial tranquillity of adolescents. This research uses a qualitative approach by applying descriptive-analytical methods. The results and discussions in this study show that zikr al-Ma'tsurat can be a solution to obtain calmness, especially in adolescent psychosocial. This study concluded that zikr al-Ma'tsurat can have an effect on improving the psychosocial calm of adolescents. This research recommends Islamic institutions and organisations to socialise to adolescents about the importance of practising zikr al-Ma'tsurat to gain tranquillity so as not to seek calm to negative things.